Functional connectivity density alterations in schizophrenia - Zhuo, Chuanjun; Zhu, Jiajia; Qin, Wen; Qu, Hongru; Ma, Xiaolei; Tian, Hongjun; Xu, Qingying; Yu, Chunshui (Frontiers in Behavioral Neuroscience, 2014)
Background: Schizophrenia is characterized by altered resting-state functional connectivity. Most previous studies have focused on changes in connectivity strengths; however, the alterations in connectivity density in schizophrenia remain largely unknown. Here, we aimed to investigate changes in resting-state functional connectivity density (rsFCD) in schizophrenia. Methods: A total of 95 schizophrenia patients and 93 sex- and age-matched healthy controls underwent resting-state functional MRI examinations. The rsFCD, which reflects the total number of functional connectivity between a given brain voxel and all other voxels in the entire brain, was calculated for each voxel of each subject. Voxel-based comparisons were performed to identify brain regions with significant rsFCD differences between patients and controls (P < 0.05, corrected). Results: Compared with healthy controls, patients with schizophrenia showed significantly increased rsFCD in the bilateral striatum and hippocampus and significantly decreased rsFCD in the bilateral sensorimotor cortices and right occipital cortex. However, the rsFCD values of these brain regions were not correlated with antipsychotic dosage, illness duration, or clinical symptom severity. Conclusions: The striatal and hippocampal regions and parietal-occipital regions exhibited completely different changes in rsFCD in schizophrenia, which roughly correspond to dopamine activity in these regions in schizophrenia. These findings support the connectivity disorder hypothesis of schizophrenia and increase our understanding of the neural mechanisms of schizophrenia.